MENINGKATKAN KETERAMPILAN BAHASA ARAB: PENERAPAN PEMBELAJARAN MAHARAH KALAM MELALUI KEGIATAN TAQDIMUL BAYAN - Jazilurrahman, Jazilurrahman; Ubaidillah, Ahmad; Fajri, Zaenol (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to understand the implementation of Taqdimul Bayan implemented at BPK Nurul Jadid Paiton Probolinggo. This research uses a qualitative research method, case study type. This research was carried out at BPK MTs. Nurul Jadid Paiton Probolinggo class VII and VIII, located in Karanganyar Village, Paiton District, Probolinggo Regency. This research was carried out from October to November 2023. The data collection technique was using the snawball sampling technique. The data sources used were primary and secondary. The informants in the research were the Chair of the BPK, BPK Arabic Language Teacher, Head of the Organization, and BPK students. Data collection techniques used participant observation, in-depth interviews and documentation. Data analysis was carried out in three stages, namely data collection, data reduction, data display, and conclusions. The results of the research show that BPK Nurul Jadid implemented it through several processes, namely: (1) Formulating Maharah Kalam Capability Standards, (2) Carrying out Taqdimul Bayan Activities , (3) Class Meeting Competition. So it is hoped that it will be able to produce the ability to develop students' anger. Through Observation methods, Interview methods and Documentation methods to become better and more inclusive. This research can provide valuable insight for Arabic language education unit institutions in developing the potential to speak Arabic fluently among students. Apart from that, the results of this research can also contribute to the literature on the Maharah Kalam Development Strategy.